Rodbina v luči srednjeveških listin - Preinfalk, Miha (Zgodovinski časopis, 2001)
Based on published and unpublished medieval documents, the article examines kinship relations and terminology pertaining to the immediate and extended family. Even though the terminology employed in these document does not basically differ from present-day terminology, there are some differences between older and more recent documents, as well as the ones in German and those in Latin. This is mainly true of expressions used to denote members of the immediate family; the names of members of the extended family are often loosely used and, since they refer to a number of kinship relations and denote frequently distant relatives or even those who are not related by blood, also somewhat inaccurate from the present point of view. For better understanding, the text also includes short genealogical tables, supplemented by more comprehensive lists, and two short "dictionaries" with Latin-Slovene and German-Slovene kinship terminology.
Keywords: history; zgodovina; genealogija; genealogy; rodoslovje; biografije; srednji vek; Middle Ages; Slovenia; Slovenija